Identification of cytotoxic copper(II) complexes with phenanthroline and quinoline, quinoxaline or quinazoline-derived mixed ligands. (15th January 2021) - Radhakrishnan, Kartikeyan; Khamrang, Themmila; Sambantham, Karpagam; Sali, Veeresh Kumar; Chitgupi, Upendra; Lovell, Jonathan F.; Mohammad, A. Akbarsha; Venugopal, Rajendiran
Graphical abstract: The mixed-ligand copper(II) complexes with quinoline/quinoxaline/quinazoline derivatives and 1, 10-phenanthroline (phen) ligands are biologically active compared to their bis-complex analogues. Remarkably, one of the quinazoline containing complexes [Cu(L5)(phen)] 2+ (L5 = 4-phenyl-2-pyridin-2-yl-quinazoline) exhibited cytotoxicity 3 times more potency than cisplatin and promote apoptosis in lung cancer cells by regulating the expression of caspase-3. Highlights: Quinoline/quinoxaline/quinazoline derivatives and phen containing Cu(II) complexes. These mixed-ligand Cu(II) complexes exhibited stronger DNA and protein binding. [Cu(quinazoline-derivative)(phen)] 2+ exhibited higher cytotoxicity than cisplatin. The same complex promotes apoptosis by regulating expression of caspase-3. Cytotoxicity of the complexes mediated by ROS production. Abstract: A series of mixed ligand copper(II) complexes, formulated as [Cu(L1-L5)(phen)(H2 O)](ClO4 )2 (1 –5), where phen =  1, 10-phenanthroline, L1 = 2-pyridin-2-yl-quinoline, L2 = 2-pyridin-2-yl-quinoxaline, L3 = 6, 7-dimethyl-2-pyridin-2-yl-quinoxaline, L4 = 4-phenyl-2-pyridin-2-yl-quinoline, and L5 = 4-phenyl-2-pyridin-2-yl-quinazoline, were synthesized and characterized. The molecular structure of 3, which alone formed into appreciable crystals, was determined by single-crystal X-ray studies, and the coordination geometry around Cu(II) was nearly square pyramidal (τ, 0.092). DNA and protein binding, DNA cleavage and in vitro cytotoxicity of the mixed ligand complexes 1 –5 were investigated and compared with their analogue bis-complexes [Cu(L1-L5)2 H2 O](ClO4 )2 6 –10 . All five mixed ligand complexes exhibited efficient DNA and protein binding, wherein 5 was the most potent. DNA cleavage studies revealed that all mixed ligand complexes engage in self-activated DNA cleavage, with 2 producing full conversion of supercoiled DNA to nicked circular form. Complex 5, with the highest DNA- and protein-binding efficiencies, demonstrated the highest cytotoxicity to A549 non-small human lung carcinoma cell (IC50  = 3.85 μM), three times more potent than cisplatin. Metal-assisted reactive oxygen species (ROS) were found to be responsible for cytotoxicity of the complexes. Fluorescent staining assays showed that all complexes induce apoptotic cell death along with some degree of necrosis. Western blot analysis of caspase-3 expression of cells exposed to Cu(II) complexes 1 and 5 revealed that both promote apoptosis, with 5 demonstrating more potency. Thus, the mixed ligand copper complexes demonstrated efficient biological activity compared to bis-complexes, with 5 holding promise for future investigation towards development as a cancer therapeutic.